The study of Quranic teaching and learning : a review in Malaysia and United Kingdom. - Che Noh, Mohd Aderi; Hussein, Amjad; Ghani, Othman; Suhid, Asmawati (IDOSI Publications, 2013)
Quranic teaching and learning is the main focus in Muslim education. The aim is to enhance students' skills in reciting, understanding and appreciating the Quran taught. This article aims to identify the teaching practice among muslim education in Malaysia and United Kingdom. The data collected can explain the level of teaching practice in Quranic Education. The results showed that the importance of the teaching components in teachers' teaching practices. For these reasons, training and courses related to Quranic teaching must be increased and taken into account by the responsible parties.